1999
DOI: 10.3109/08820539909069540
|View full text |Cite
|
Sign up to set email alerts
|

Laser Treatment of Diabetic Macular Edema: Comparison of ETDRS-Level Treatment with Threshold-Level Treatment by Using High-Contrast Discriminant Central Visual Field Testing

Abstract: Grid laser is recognized as an extremely effective treatment of diabetic macular edema, although it causes significant chorioretinal damage when applied and scars that expand with time. The purpose of this study is to compare the effects of two methods of grid laser photocoagulation for diabetic macular edema on high-contrast target discrimination in the central visual field. Grid laser photocoagulation with the Early Treatment Diabetic Retinopathy Study intensity burns has previously been shown to cause full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Focal and grid laser photocoagulation is an effective treatment of macular edema, but also causes scotomata and scarring (Morgan and Schatz, 1989;Schatz et al, 1991;Early Treatment Diabetic Retinopathy Study Research Group, 1995). Laser burns can enlarge postoperatively and cause choroidal neovascularization (Lewen, 1988;Lewis et al, 1990), subretinal fibrosis (Guyer et al, 1992;Rutledge et al, 1993;Lövestam-Adrian and Agardh, 2000), and additional visual field loss (Striph et al, 1988;Hudson et al, 1998;Ishiko et al, 1998;Mainster, 1999;Sinclair et al, 1999). Over time, loss of one class of retinal cells may, by trans-synaptic degeneration and associated inflammation, result in the loss of other retinal neurons (Stone, 1950;Birnbach et al, 1994) and RPE remodeling (Framme et al, 2009) or retinal remodeling (Marc et al, 2007).…”
Section: Potential Improvement Of Retinal Laser Therapymentioning
confidence: 99%
“…Focal and grid laser photocoagulation is an effective treatment of macular edema, but also causes scotomata and scarring (Morgan and Schatz, 1989;Schatz et al, 1991;Early Treatment Diabetic Retinopathy Study Research Group, 1995). Laser burns can enlarge postoperatively and cause choroidal neovascularization (Lewen, 1988;Lewis et al, 1990), subretinal fibrosis (Guyer et al, 1992;Rutledge et al, 1993;Lövestam-Adrian and Agardh, 2000), and additional visual field loss (Striph et al, 1988;Hudson et al, 1998;Ishiko et al, 1998;Mainster, 1999;Sinclair et al, 1999). Over time, loss of one class of retinal cells may, by trans-synaptic degeneration and associated inflammation, result in the loss of other retinal neurons (Stone, 1950;Birnbach et al, 1994) and RPE remodeling (Framme et al, 2009) or retinal remodeling (Marc et al, 2007).…”
Section: Potential Improvement Of Retinal Laser Therapymentioning
confidence: 99%
“…The Branch Vein Occlusion Study Group demonstrated that grid laser photocoagulation is effective in reducing the visual acuity loss due to MO secondary to BRVO 2. Unfortunately, conventional grid laser treatment leads to a very limited improvement of visual acuity,2 and may be associated with the occurrence of several complications, including enlargement of laser scar,3 – 5 choroidal neovascularisation,6 7 subretinal fibrosis,8 – 11 and visual-field sensitivity deterioration 1217…”
mentioning
confidence: 99%
“…13 The device was developed to improve the measurement of visual performance in eyes with macular disease under luminance, hue, and contrast conditions that simulate conditions encountered in normal tasks of daily living.…”
Section: Introductionmentioning
confidence: 99%